A Study on Web Content Mining (International Journal of Engineering and Computer Science, 2017)
Web Mining is extracting information from the web re-sources and finding interesting patterns that can be useful from ever expanding database of World Wide Web. Whenever we talk about data, we conclude that there is a huge range of data on World Wide Web. Due to heterogeneity and unstructured nature of the data available on the WWW, Web mining uses various data mining techniques to discover useful knowledge from Web hyperlinks, page content and usage log. Web Content Mining is a component of Data Mining. The main uses of web content mining are to gather, categorize, organize and provide the best possible information available on the Web to the user requesting the information. This paper deals with a preliminary discussion of Web content mining, contributions in the field of web mining, the prominent successful tools and algorithms.